Role of Histidine-86 in the Catalytic Mechanism of Ferredoxin: Thioredoxin Reductase - Walters, Elizabeth M.; Garcia-Serres, Ricardo; Naik, Sunil G.; Bourquin, Florence; Glauser, Dominique A.; Schürmann, Peter; Huynh, Boi Hanh; Johnson, Michael K. (My University, 2009)
Ferredoxin:thioredoxin reductase catalyzes the reduction of thioredoxins in plant chloroplasts using the [Fe2S2] ferredoxin as a one-electron donor and as such plays a central role in light regulation of oxygenic photosynthesis. The active-site comprises a [Fe4S4] cluster next to a redox-active disulfide that is cleaved in sequential one-electron steps and the combination of spectroscopic and crystallographic studies have revealed a catalytic mechanism involving novel site specific cluster chemistry in the oxidized, one-electron- and two-electron-reduced redox states. Histidine-86 has emerged as a potential proton donor/acceptor in the catalytic mechanism based on redox-related changes in the positioning of the imidazole ring during redox cycling and greatly decreased activity for the H86Y variant. Here we report on spectroscopic and redox characterization of the [Fe4S4] center in Synechocystis sp. PCC 6803 H86Y ferredoxin:thoredoxin reductase in the accessible redox states of both the as purified and N-ethylmaleimide-modified forms, using the combination of UV−visible absorption and variable-temperature magnetic circular dichroism, EPR, resonance Raman and Mössbauer spectroscopies. The results demonstrate that His86 is required for formation of the partially valence-localized [Fe4S4]2+ cluster that is the hallmark of two-electron-reduced intermediate. Taken together with the available structural data, the spectroscopic results indicate a functional role for His86 in protonation/deprotonation of the cluster-interacting thiol and anchoring the cluster interacting thiol in close proximity to the cluster in the two-electron-reduced intermediate.